I-CReST 2020 International Conference on Research and Practices in Science, Technology and Social Sciences: proceedings book - Razman, Nur Izzatie Hannah (Center of Foundation Studies, 2020)
Centre of Foundation Studies is pleased to announce its International Conference (I-CReST 2020) that will be held on 4th July 2020. With the theme, “Harnessing Potential and Leading Transformational Change”, the conference will provide a platform for undergraduates and postgraduate students, academics, researchers, professionals and industrial practitioners from various backgrounds to share ideas and research findings in their respective fields.